Research Progress on the Application of Coffee Grounds in Capacitor Electrode Materials - Zhang, Jianqiang; Kan, Xurundong; Liu, Zaiqiong (International Journal of Mechanical and Electrical Engineering, 2025)
This paper explores the innovative use of coffee grounds as electrode materials in capacitors, addressing the need for sustainable and efficient energy storage solutions. The study begins with an examination of the properties of coffee grounds, focusing on their chemical composition and structural characteristics that make them suitable for electrode applications. Various preparation methods are discussed, highlighting techniques to optimize the physical and electrochemical properties of coffee grounds to enhance their performance as electrode materials. The research delves into the practical applications of coffee grounds in capacitor electrodes, providing insights into their potential to replace conventional materials. This includes an analysis of their electrical conductivity, stability, and energy storage capacity, emphasizing the environmental benefits and cost-effectiveness of using a waste product like coffee grounds. The results demonstrate the feasibility of coffee grounds as a viable alternative in the development of sustainable capacitor technologies. The study concludes by considering the future perspectives and potential advancements in this field, suggesting areas for further research to overcome current limitations and improve the performance of coffee ground-based electrode materials. This work contributes to the broader effort of integrating waste materials into high-value applications, promoting environmental sustainability and resource efficiency in energy storage systems.